2010
DOI: 10.1002/pmic.200900464
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics to proteomics: From yeast to brain

Abstract: Brain is the most complex and least understood organ of the body. Recent research suggests that epigenetics of the brain may be behind the complex functions of this master organ. Yeast, the simplest eukaryote, had been the model for studying the complex physiology of higher eukaryotes, including humans. Current depth in understanding of mechanisms of gene regulation has been possible mainly because of the knowledge acquired by epigenetic studies on yeast while the research on the biochemistry and physiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 249 publications
(279 reference statements)
0
2
0
Order By: Relevance
“…Yeasts have been used as models for higher level complex organisms, including mammals and humans 40 . Whole-genome sequencing studies have shown that yeasts have similar genome size, gene content, and colinearity of genes along the chromosomes of species 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Yeasts have been used as models for higher level complex organisms, including mammals and humans 40 . Whole-genome sequencing studies have shown that yeasts have similar genome size, gene content, and colinearity of genes along the chromosomes of species 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic approaches have been used as strong tools to find the global interacting partners of many complexes (24)(25)(26)(27). Therefore, in order to find the possible regulatory partners of the pol III TC, we followed AP-MS proteomic approaches (28) wherein we selected one subunit of each component to pull down the interacting partners in its transcriptionally active and repressed (nutrient starvation) states.…”
Section: Introductionmentioning
confidence: 99%